A study on the effects of ATIGA on the bilateral trade flows of the ASEAN countries and its top 8 trading partners on the medical device industry - Aldana, Carl Francis (Animo Repository, 2022)
The implementation of the ASEAN Trade in Goods (ATIGA) in 2010 lowered tariffs, quantitative restrictions, and non-tariff measures within the ASEAN region. It was to promote regional trade and competitiveness for the region to be a production base towards the global market. The initiative prioritized 12 sectors that were important to the ASEAN trade, one of them was the healthcare products sector. The medical device industry of the ASEAN, a subsector of the healthcare products, was seen to be inefficient. Studies tackled the effects of Preferential Tariff Agreements on intra-ASEAN trade, while only few studied its effects on the trade integration and comparative advantage on the medical device industry. The Gravity Model and Panel Regression analysis was used to capture the effects of ATIGA to the medical device industry. Data between 2004-2019 and was acquired from online databases such as the UN comtrade database, CEPII, ASEANstats portal, and the Worldbank database. With this, the study determined whether ATIGA has an effect on the trade and comparative advantage of the medical device industry of the ASEAN-x countries. Results show that the creation of the ATIGA has a significant positive effect on medical device trade within the ASEAN, which implies that pure trade creation was reflected from this agreement. This was further backed up by the results of the RCA and IIT indices where results show that most ASEAN countries have increased index values. This implies that the comparative advantage and trade integration of the medical device industry within the ASEAN has been boosted by the ATIGA.